Determination of Abraham model solute descriptors for xanthone based on experimental solubility measurements at 298.2 K. (3rd March 2020) - Qian, Ellen; Lee, Grace; Che, Melanie; Wang, Lainey; Yue, David; Fischer, Rachel; Jodray, Megan; Gupta, Avi; Neal, Reese; Liu, Yuqing; Acree, William E.; Abraham, Michael H.
ABSTRACT: Experimental solubilities have been determined for xanthone dissolved in 15 different alcohol solvents (ethanol, 1-propanol, 1-butanol, 1-pentanol, 1-hexanol, 1-heptanol, 1-octanol, 2-methyl-1-propanol, 3-methyl-1-butanol, 2-ethyl-1-hexanol, 2-propanol, 2-butanol, 4-methyl-2-pentanol, 2-methyl-2-propanol and 2-methyl-2-butanol), in five alkyl acetate solvents (methyl acetate, ethyl acetate, propyl acetate, butyl acetate and pentyl acetate), in diisopropyl ether and in 2-ethoxyethanol at 298.2 K. In total, solubility measurements were performed in 22 organic solvents of varying polarity and hydrogen-bonding character. Results of the experimental measurements were used to calculate the Abraham model solute descriptors for xanthone. The calculated solute descriptors describe the experimental solubility data to within 0.096 log units.